1971
DOI: 10.1139/y71-116
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cardiac Pacing at High Rates on Plasma Enzyme Levels in the Anesthetized Dog

Abstract: In pentobarbital-anesthetized dogs, cardiac pacing by an intra-atrial electrode at 240 beats/min resulted in small but significant increases in the plasma activity of glutamic–oxalacetic transaminase, which returned to control values within 30 min. No change in plasma creatine phosphokinase was observed following pacing. Possible mechanisms responsible for the release of tissue enzyme during pacing include an increase in rate of deformation of, and an increase in substrate transport by, the cardiac muscle plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1974
1974
1983
1983

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…From this general formulation, whose limitations have been discussed above, it is questionable whether enzymes in heart and muscle reach the intravascular space directly, äs proposed by several authors (31)(32)(33)(34)(35)(36)(37)(38)(39)(40).…”
Section: Lymph Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…From this general formulation, whose limitations have been discussed above, it is questionable whether enzymes in heart and muscle reach the intravascular space directly, äs proposed by several authors (31)(32)(33)(34)(35)(36)(37)(38)(39)(40).…”
Section: Lymph Formationmentioning
confidence: 99%
“…The lymphatic pathway, however, is called in question by Bolter & Critz (39,40) and Szabo et al (36,37,38). Indications were found that the Interruption of blood flow to skeletal muscle for one hour did not result in an enzyme release from muscle cells.…”
Section: Significance Of Extracellular Distribution and Transport Of mentioning
confidence: 99%